Hydrothermal alteration and structural lineaments of the Cambrian Jbel Boho volcanic system (Bou Azzer inlier, Morocco) revealed by remote sensing: Implications for an atypical porphyry-style Cu system - Malika Fadil; Hassan Ibouh; Nasrrddine Youbi; El Mostafa Mouguina; Loubna Ait Jana; Jihane Ounar; Hassan Admou; El Hassane Chellai; Hind Elhachimi; Sandro Conticelli; Claudio Natali; Lhou Maacha; et al. (Journal of African Earth Sciences, 2026)

Distinct mantle metasomatism in the mantle source of ultrapotassic magma revealed by CaBa isotopes - Yu Chen; Yi-Xiang Chen; Xiao-Feng Gu; Riccardo Avanzinelli; Sandro Conticelli (Chemical Geology, 2026)

Application of Red Relief Image Maps as a complementary tool for mapping volcanic areas: The case of the Monte Amiata volcano, Italy - José Pablo Sepúlveda; Simone Paternostro; Lucrezia Valeriani; Giulio Masetti; Alvaro Aravena; Stefano Lo Faro; Letizia Vita; Sandro Conticelli; Raffaello Cioni (Geomorphology, 2026)

Mg-Zn isotopes track the role of recycled sediment composition in shifting silica-saturated to silica-unsaturated ultrapotassic rocks from the Central Mediterranean - Yu Chen; Yi-Xiang Chen; Sheng-Ao Liu; Shan Ke; Riccardo Avanzinelli; Sandro Conticelli (Chemical Geology, 2024)

The geochemistry of leucite-bearing lavas from early stages of the Somma-Vesuvius volcanic complex: Feeder systems and mantle enrichment processes in the Neapolitan district of the Roman Magmatic Province - Vincenza Guarino; Roberto Solone; Martina Casalini; Luigi Franciosi; Luigi Dallai; Vincenzo Morra; Sandro Conticelli; Leone Melluso (Geochemistry, 2024)

Calcium isotope compositions of subduction-related leucite-bearing rocks: Implications for the calcium isotope heterogeneity of the mantle and carbonate recycling in convergent margins - Huange Ren; Martina Casalini; Sandro Conticelli; Chunfei Chen; Stephen F. Foley; Lanping Feng; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

From subduction to strike slip-related volcanism: insights from Sr, Nd, and Pb isotopes and geochronology of lavas from Sivas–Malatya region, Central Eastern Anatolia - Paolo Di Giuseppe; Samuele Agostini; Gianfranco Di Vincenzo; Piero Manetti; Mehmet Yilmaz Savaşçın; Sandro Conticelli (International Journal of Earth Sciences, 2021)
Anatolia is characterised by a complex geodynamic evolution, mirrored by a wide spectrum of magmatism. Here, we investigated the timing and the geochemical/isotopic characters of the Miocene to Pliocene volcanism of Sivas–Malatya Region (Central Eastern Anatolia), and its relationships with local and regional tectonics. Na-alkaline basaltic lavas were emplaced during middle Miocene at Sivas (16.7–13.1 Ma), in the North, whilst transition from calc-alkaline to Na-alkaline rocks is observed at Yamadağ and Kepez Dağ volcanic complexes. Calc-alkaline products erupted during early to middle Miocene, and more precisely from 19.5 to 13.6 Ma at Yamadağ and from 16.4 to 13.5 Ma at Kepez Dağ, with final Na-alkaline activity of the Arguvan volcanic field lasting till late Miocene (15.7–10.6 Ma). Volcanism renewed during the Pliocene in the Kangal (5.9–4.0 Ma) volcanic field with the emission of K-alkaline igneous rocks. Mafic calc-alkaline and Na-alkaline rocks partially overlap in age but can be easily distinguished by their petrochemical characters. Mafic calc-alkaline igneous rocks show typical subduction-related petrological and geochemical affinities. They are both two-pyroxene or clinopyroxene and amphibole-bearing rocks, characterised by high LILE/HFSE values, with variable 87 Sr/ 86 Sr i (0.70396–0.70539) and 143 Nd/ 144 Nd i (0.51260–0.51287). Mafic Na-alkaline igneous rocks are characterised by big olivine phenocrysts and show intraplate geochemical flavours, although some LILE depletion with respect to HFSE as well as variable 87 Sr/ 86 Sr i (0.70347–0.70553) and 143 Nd/ 144 Nd i (0.51261–0.51291) isotopic compositions are present. These characteristics are suggestive for the occurrence, at some stage of their genesis, of a possible interaction with subduction-related reservoirs. The Kangal K-alkali basalts still show intraplate-like petrological and geochemical affinities with LILE/HFSE ratios similar to those of the Miocene Na-alkaline rocks, and largely variable 87 Sr/ 86 Sr i (0.70425–0.70520) and 143 Nd/ 144 Nd i (0.51262–0.51277) isotopic compositions, overlapping the arrays observed in the earlier stages of volcanism. A general transition from calc-alkaline to Na-alkaline volcanic rocks is observed with time, according to the evolution of the geodynamics of the Anatolia region. Early to middle Miocene calc-alkaline magmas were derived by partial melting of the mantle wedge delimited by the subduction of the last oceanic branch of Neotethys. The Na-alkaline magmas, on the other hand, were generated within the asthenospheric mantle beneath the slab and migrated through slab tears into the mantle wedge where they mixed with subduction-related components. The subduction-related component decreased with time and transitional magmas are found in the youngest activity of Yamadağ and Kepez Dağ, shortly followed by clear within-plate lavas formed in the Arguvan volcanic field. The appearance of the youngest K-alkaline volcanic rocks in the Kangal basin represents an abrupt change in the magma supply at depth, although continental crustal contamination en-route to the surface played an important role in their genesis.

High-Nb hawaiite–mugearite and high-Mg calc-alkaline lavas from northeastern Iran: Oligo-Miocene melts from modified mantle wedge - Parham Ahmadi; Mohammad Reza Ghorbani; Massimo Coltorti; Takeshi Kuritani; Yue Cai; Anna Maria Fioretti; Eleonora Braschi; Pier Paolo Giacomoni; Farzaneh Aghabazaz; Shahrouz Babazadeh; Sandro Conticelli (International Geology Review, 2019)

Sr-Nd-Pb isotopes from the Radicofani Volcano, Central Italy: constraints on heterogeneities in a veined mantle responsible for the shift from ultrapotassic shoshonite to basaltic andesite magmas in a post-collisional setting - Sandro Conticelli; Riccardo Avanzinelli; Sara Marchionni; Simone Tommasini; Leone Melluso (Mineralogy and Petrology, 2011)

Isotope geochemistry (Sr–Nd–Pb) and petrogenesis of leucite-bearing volcanic rocks from “Colli Albani” volcano, Roman Magmatic Province, Central Italy: inferences on volcano evolution and magma genesis - Elena Boari; Riccardo Avanzinelli; Leone Melluso; Guido Giordano; Massimo Mattei; Arnaldo A. De Benedetti; Vincenzo Morra; Sandro Conticelli (Bulletin of Volcanology, 2009)

Shoshonite and sub-alkaline magmas from an ultrapotassic volcano: Sr–Nd–Pb isotope data on the Roccamonfina volcanic rocks, Roman Magmatic Province, Southern Italy - Sandro Conticelli; Sara Marchionni; Davide Rosa; Guido Giordano; Elena Boari; Riccardo Avanzinelli (Contributions to Mineralogy and Petrology, 2009)